Telaah Yuridis terhadap Putusan Mahkamah Konstitusi Nomor: 92/PUU-XXII/2024 dalam Perkara Pengujian Undang-Undang Desa - Muh. Fadil; Ahmad Rustan; Multi Sri Asnani (Jurnal Hukum Lex Generalis, 2025)
The simultaneous election of Village Heads (Pilkades) in South Konawe Regency on September 24, 2023 is crucial after the issuance of Law Number 3 of 2024. Although the Constitutional Court in Decision Number 92/PUU-XXII/2024 stated that the Regional Elections were in accordance with Law Number 6 of 2014 concerning Villages, the facts are contrary to Article 32 paragraph 1 of the Village Law regarding the notification of the end of the term of office of the village head. This research aims to analyze the Constitutional Court's considerations in case 92/PUU-XXII/2024 from the perspective of justice and the principle of the rule of law. This research employs a normative legal method, utilizing both a statutory approach and a case approach, with a focus on examining Article 118, letter e of Law Number 3 of 2024. The Constitutional Court judge's consideration that the Regional Elections in South Konawe were by the Village Law factually contradicted Article 32 paragraph 1 of Law Number 6 of 2014. A total of 94 village heads still have 7 months remaining in office and 2 other village heads 14 months when the election is held, even though the notice of term of office should have been made 6 months in advance. This makes the Constitutional Court's consideration juridically flawed and contrary to the principle of the rule of law, so that the applicant's application should be rejected.